Phytoplasmas diversity and identification of new aster yellows subgroup (16SrI) associated with weed species in Argentina - Fernandez, Franco Daniel; Galdeano, Ernestina; Conci, Luis Rogelio (Microbiology Society, 2021)
Symptoms of phytoplasma infection were observed in different weed species, Bidens subalternans, Conyza bonariensis, Heterosperma ovatifolium and Conium maculatum, collected from diverse geographical regions in Argentina. To confirm the association of phytoplasma infection with symptomatic plants, PCR, RFLP and phylogenetic analyses based on 16S rRNA-encoding sequences were performed. In this work, we report the presence of phytoplasmas from group 16SrVII (subgroup 16VII-B) infecting C. bonariensis and B. subalternans and from group 16SrIII (subgroup 16SrIII-X) B. subalternans, H. ovatifolium, and C. maculatum. Phytoplasmas from the aster yellows group were detected infecting C. bonariensis and B. subalternans. Analysis of 16S rRNA-encoding genes revealed the presence of two distinct operons, rrnB (16SrI-B) and newly described rrnA, which is different from the reference RFLP patterns of all previously established 16SrI-subgroups. A single rp operon sequence analysis reveals the presence of simple infection and confirms a description of a novel subgroup. On the basis of these results we propose a designation of new subgroup 16SrI-( B/AJ) AJ (rp-AJ). To our knowledge, this is the first report of phytoplasmas infecting Bidens subalternans¸ Heterosperma ovatifolium and Conium maculatum.